Experiencia: aceptabilidad del uso de simulación clínica en educación médica: la experiencia del curso Síntesis de Conocimientos en Medicina - George C., Sergio; Cuadrado N., Cristóbal; Solar A., Ignacio; Peralta C., José; Sanhueza G., Hugo; Bascuñán A., Josefina (Revista Hospital Clínico Universidad de Chile, 2014)
Clinical simulation is a technique with multiple benefits. Supervised professional practice results the best predictor of performance quality of a determined clinical skill. The “Summary of Medical Knowledge” course considers within its objectives enhancing necessary clinical skills before graduating, which is done through clinical simulation. Materials and methods: Voluntary participating activity was developed, considering performance in 5 clinical stations, which were assessed by Objective Structured Clinical Examination (OSCE). This activity was held at the Clinical Skill Centre, Faculty of Medicine, University of Chile. The evaluated skills were chosen based on information provided by graduates 2010-2012 about their own perception of competences. Results: 89 students and 53 teachers participated voluntarily. Over 90 % of respondents (both teachers and students) stated that the activity was a great contribution to become aware of their own skills and limitations, resulting relevant and essential for medical training. Discussion: Simulation is feasible as a method of training in undergraduates, with a high rate of satisfaction for both students and teachers, encouraging the acquisition of clinical skills.